091 If we Build It, Will you Search for It? Finding Multiple Chronic Condition Guidelines in the National Guideline Clearinghouse. (15th August 2013) - Haskell, L; Jue, J.; Cunningham, S.; Nix, M.; Coates, V.
Abstract : Background: In the US, it is estimated more than 25% of Americans have multiple chronic conditions (MCCs) and their care accounts for approximately 66% of total health care spending. Few clinical practice guidelines address MCCs. Objectives: Determine the number and scope of guidelines represented in the National Guideline Clearinghouse (NGC), funded by the Agency for Healthcare Research and Quality, addressing MCCs and provide strategies to identify these guidelines and facilitate quick retrieval by NGC users. Methods: We searched for guidelines within NGC to identify those that address MCCs. We characterised these guidelines defining the number and type of MCCs addressed, the number of recommendations addressing MCCs, whether they addressed treatment, diagnosis, prevention or counselling, whether they graded the level of evidence, and whether the MCCs were concordant/discordant with the guideline's primary disease/condition. Results: Final analysis of information collected and recommendations and strategies for facilitating retrieval of this content in NGC will be completed by June 2013. Discussion: Traditionally, guidelines focus on individual diseases so their application to the growing MCC population is limited. At the same time, evidence supporting recommendations for MCCs is lacking. Although our preliminary findings indicate that there are some guidelines addressing MCCs, there has been no obvious way to locate them on NGC. Implications for Guideline Developers/Users: Guideline developers need to create guidelines addressing MCCs. NGC aims to create ways to highlight MCC guidelines and make them easier to find and use.